2018
DOI: 10.1080/15295036.2018.1516046
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative insights into televised birth: a content analysis ofOne Born Every Minute

Abstract: This article explores birth representations through a content analysis of two seasons of the U.K. program, One Born Every Minute ( OBEM ) (Channel 4, 2010–). Reality television (RTV) has been a fertile ground for the mediation of birth, but has also stoked controversy among feminist critics and the birth community about how birth is represented and the impacts this might have for women and society. International research has explored problematic over-representation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
2
13
0
1
Order By: Relevance
“…Teijlingen et al (2009) suggest high-income countries separate birth from normal life, which reduces understanding of physiology and results in acceptance that birth, as portrayed by the mass media, is dangerous and requires technology. This is supported by De Benedictis et al's. (2018) content analysis of a popular maternity television series that reported 77% of births depicted a procedure occurring, of which 91% did not show facilitation of choice.…”
Section: Socio-cultural Perceptionssupporting
confidence: 66%
“…Teijlingen et al (2009) suggest high-income countries separate birth from normal life, which reduces understanding of physiology and results in acceptance that birth, as portrayed by the mass media, is dangerous and requires technology. This is supported by De Benedictis et al's. (2018) content analysis of a popular maternity television series that reported 77% of births depicted a procedure occurring, of which 91% did not show facilitation of choice.…”
Section: Socio-cultural Perceptionssupporting
confidence: 66%
“…Our findings suggest that women's birth preferences may be affected by the COVID‐19 pandemic and that pandemic‐related stress can contribute to shifts in childbirth practices. Women may choose where to give birth based on risk perceptions, 39‐41 with common notions that giving birth in a hospital is the safest option 42‐45 . However, the possibility of contracting the virus in the hospital appears to be shifting pregnant people's risk perceptions in complex ways that intersect with a range of pregnancy‐related beliefs and stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has examined representations of birth, infertility, and related topics in the media (Benedictis et al, 2019; Tyler and Clements, 2009), for example, finding that women are shown to not have control over their birth interventions on TV (Benedictis et al, 2019). In the online context, Das (2017) shows how traumatic and difficult birth stories are silenced, highlighting an aversion to sharing and hearing difficult stories.…”
Section: Discussionmentioning
confidence: 99%